Theoretical and methodological bases of assessment of sustainable development of rural areas - Tasmaganbetov, A.B.; Abayev, A.A.; Rahmanova, A.S.; Tleukabylova, K.B. (KSU Publ., 2019)
The article considers the features of the assessment of sustainable development of rural areas taking into account the economic, social, environmental and institutional factors of the region. The main attention is paid to the indicator of socio-economic development of rural areas: gross regional product, actual final consumption of households, wages of employees, net taxes on production and others. According to the authors, to build the index, it is necessary to choose adequate indicators that will reflect the criterion of competitiveness and progressiveness of the industry structure. At the same time, it can be statistically available for evaluation. The article notes that for qualitative and quantitative assessment of sustainable development of rural areas should be used critical factors: economic capital, environmental resources, technical systems, geographical infrastructure, social infrastructure. The article defines «indicative plan-forecast» as the main tool of the strategy of sustainable development of rural territories. This reflects the most important priorities of socio-economic development of rural territories, methods and instruments of influence of state bodies on socio-economic development, the necessary volumes of economic resources. According to the authors, to assess the sustainable development of rural areas, it is necessary to calculate the indices taking into account the specifics of the competitiveness of regions and to determine the factors on the basis of the available analytical base.
Ауылдық аумақтардың тұрақты дамуын бағалаудың теориялық жəне əдістемелік негіздері
Теоретические и методические основы оценки устойчивого развития сельских территорий
Keywords: sustainable development; rural areas; indicator; economic factors; environmental factors; social factors; infrastructure